State reform in Latin America: current situation and future challenges - Bandeira, Pablo (Iberoamerican Journal of Development Studies, 2015)
Since the "third wave of democracy" started in the late 70s, there has been an intense process of political reform in Latin America. This article first analyzes the results of these reforms in the areas of citizen public participation, tax collection, the professionalization of the civil service and the effectiveness of the judicial system in the various countries of the region. Second, it identifies the main issues that still need to be reformed in these areas, and finally, discusses how these reforms can be carried in order to achieve the expected results.
Keywords: political reforms; Latin America; citizen participation; tax collection; public administration; judicial system